The Method of Dialectic and the Ethics of Dialogue in Islamic Thought. (Comprehensive Journal of Science, 2026)
Allah, exalted be He, created human beings diverse and different in their colors, forms, and intellects. It is therefore natural that an individual encounters, in the course of life, others who differ from them in creed, thought, or opinion. When a person seeks to engage with someone who holds a differing view, the only viable path is dialogue—conducted in the best and most gracious manner—in order to seek truth or to defend one’s beliefs.Based on this premise, the present study—The Method of Dialectic and the Ethics of Dialogue in Islamic Thought—explores the reality of human diversity in beliefs and ideas, and the consequent necessity of communication through dialogue grounded in evidence and rational proof.The Qur’an has established dialogue as an essential methodology founded on intellectual and emotional persuasion, distanced from coercion and fanaticism. This gives Qur’anic dialogue a distinctive character that sets it apart from Greek philosophical dialectic.The central research question therefore arises: Does Islamic dialectic possess a unique nature that distinguishes it from Greek philosophical dialectic? The importance of this study lies in clarifying how Muslim jurists and thinkers were influenced by the Qur’anic method in their practice of debate and dialogue with others.The study aims to uncover the impact of the Qur’anic methodology in shaping the dialogical practices of Muslim thinkers, and to highlight the moral and human foundations upon which this method is built.The research employs a descriptive, analytical, and inductive methodology that classifies facts, analyzes them, and connects them to Qur’anic texts and intellectual practices.The findings conclude that dialogue and dialectic in Islamic thought constitute an integrated Qur’anic methodology designed to establish truth through evidence and proof, and grounded in firm ethical and human values.
Keywords: Dialectic – Dialogue – Islamic Thought – Ethics of Dialogue – The Holy Qur’an.